HELMINTH COMMUNITY OF BACKYARD CHICKENS (GALLUS GALLUS DOMESTICUS LINNAEUS, 1758) IN SEROPÉDICA, RIO DE JANEIRO, BRAZIL - de Oliveira Simões, Raquel (2021)
The domestic chicken, Gallus gallus domesticus Linnaeus, 1758, is an important component of theagribusiness segment, and Brazil is one of the world's largest broiler producers and exporters. The present study aimed to characterize the composition and structure of the helminth community of backyard chickens, G. g. domesticus, in Seropédica, Rio de Janeiro, Brazil. Fifty-five adult chickens were studied. The overall helminth species richness was 12. The nematodes Capillaria sp. And Heterakis gallinarum (Schrank, 1788), recovered from small intestine and cecum, respectively, presented the highest prevalence and mean abundance. In addition, these species presented the highest values of frequency of dominance. The helminth species Amoebotaenia cuneata (von Linstow, 1872) – Raillietina tetragona (Molin, 1958); and Davainea proglottina (Davaine, 1860) – A. cuneata; and H. gallinarum – Capillaria sp. showed significant positive correlation between their abundance and prevalence. Gongylonema ingluvicola Ransom, 1904 and H. gallinarum showed significant correlation between host sex and helminth abundance, while there was no correlation between host sex and helminth prevalence. The knowledge of helminth community structure in free-range chickens is important to adopt better measures for control and prevention of helminth infections.